Robert Delpire, un précurseur dans l’édition pour la jeunesse des années 1950-1970 - Michèle Piquard (Strenae)
In this paper, I will attempt to demonstrate how certain disparate factors can explain the relatively steady production among children’s book publishers from the beginning of the 1950s through the middle of the 1960s, its subsequent revival throughout the following ten years, and the pioneering role Robert Delpire played in this industry.